Amyand's Hernia. Case Report - Joel Ramos Rodriguez; Javier Cruz Rodríguez; Carlos Ramírez León; Marcia O´Farril Hernández (Medisur)
Amyand's hernia is a rare disease generally diagnosed during the surgical act. Its incidence is between the 0, 28-1 %. The proposed treatment of election is the appendectomy through a herniotomy with primary reparation of the hernia using the same incision. It is presented an 85 year old male patient’s case who was hospitalized for surgical treatment with diagnosis of impacted right inguinal hernia and Amyand's hernia was diagnosed in the operative act. He had a satisfactory evolution. It was decided to report the case for being an uncommon entity.